Corporate Networks and Business Groups in Argentina in the Early 1970s - Lluch, Andrea Mari (2014)
This article examines the interlocking directorates' structure of prominent Argentine business groups at the end of the import substitution period (1970–72), identifying corporate relations among and between business groups and the largest companies, during a period characterised by high institutional and macroeconomic instability. Applying social network analysis, it seeks to clarify how business groups can contribute to the cohesion of a corporate network structure, through their ability to create links among firms not only within their boundaries but also external to them. The article contributes to both corporate network and business groups' literature, highlighting a role of business groups that extant literature has failed to identify as relevant.